The history of the "fast sound" in liquid water - Ruocco, G.; Sette, F. (Condensed Matter Physics, 2008)
This paper aims to discuss the present understanding of the high frequency dynamics in liquid water, with particular attention to a specific phenomenon – the so-called fast sound – since its first appearance in the literature up to its most recent explanation. A particular role in this history is played by the inelastic x-ray scattering (IXS) technique, which – with its introduction in the middle ’90- allowed to face a large class of problems related to the high frequency dynamics in disordered materials, such as glass and liquids. The results concerning the fast sound in water obtained using the IXS technique are here compared with the inelastic neutron scattering (INS) and molecular dynamics simulation works. The IXS work has allowed us to demonstrate experimentally the existence of two branches of collective modes in liquid water: one linearly dispersing with the momentum (apparent sound velocity of =3200 m/s, the “fast sound”) and the other at almost constant energy (5÷7 meV). It has been possible to show that the dispersing branch originates from
the viscoelastic bend up of the ordinary sound branch. The study of this sound velocity dispersion, marking a transition from the ordinary sound, c₀ to the “fast sound”, c₀₀, as a function of temperature, has made it possible to relate the origin of this phenomenon to a structural relaxation process, which presents many analogies to those observed in glass-forming systems. The possibility to estimate from the IXS data the value of the relaxation time, , as a function of temperature leads to relating the relaxation process to the structural re-arrangements induced by the making and breaking of hydrogen bonds. In this framework, it is then possible to recognize an hydrodynamical “normal” regime, i. e. when one considers density fluctuations whose period of oscillation is on a timescale long with respect to , and a solid-like regime in the opposite limit. In the latter
regime, the density fluctuations feel the liquid as frozen and the sound velocity is much higher: this is “fast sound” whose value is equivalent to the sound velocity found in crystalline ice. Стаття має на метi обговорити сучасне розумiння високочастотної динамiки у водi з наголосом на специфiчне явище – так званий швидкий звук – вiд його першої появи в лiтературi аж до недавнiх пояснень. Особливу роль у цiй iсторiї вiдiграла методика непружнього розсiяння рентгенiвських променiв (НРРП), яка – вiд її впровадження у серединi 90-х рокiв – започаткувала великий клас задач, пов’язаних з високочастотною динамiкою неспорядкованих систем, таких як стекла та рiдини. Результати по швидкому звуку в водi, отриманi методикою НРРП, тут порiвнюються з роботами по непружньому розсiянню нейтронiв та моделюванню методом молекулярної динамiки. Роботи з НРРП дозволили експериментально продемонструвати iснування у водi двох вiток колективних мод: одна з лiнiйною дисперсiєю (зi спостереженою швидкiстю звуку 3200 м/с, “швидкий звук”) та iншу з майже постiйною енергiєю (5÷7 меВ). Показано, що вiтка з дисперсiєю походить вiд в’язкопружнього згину звичайної акустичної вiтки. Дослiдження цiєї дисперсiї швидкостi звуку, що визначає перехiд вiд звичайного звуку , c₀ до “швидкого звуку”, c₀₀, як функцiя температури, дозволила пов’язати природу цього явища з процесом структурної релаксацiї, що представляє багато аналогiй зi спостережуваними у склоутворюючих системах. Можливiсть визначити з даних НРРП значення релаксацiйного часу, τ, як функцiї температури приводить до пов’язання релаксацiйного процесу зi структурною перебудовою, iндукованою створенням та розривом водневих зв’язкiв. В рамках такого пiдходу є можливим визначити гiдродинамiчний “нормальний” режим, коли розглядаються флуктуацiї густини з довгим перiодом осциляцiй по вiдношенню до τ, та твердотiльний режим у протилежнiй границi. В останньому режимi флуктуацiї густини вiдчувають рiдину як заморожену, а швидкiсть звуку є набагато бiльшою: це є “швидкий звук” з величиною еквiвалентною швидкостi звуку знайденою в кристалiчному льодi.